Integrating STEM Vocabulary into English Language Teaching: Challenges and Renewable Energy Potential in the Department of Electrical Engineering - Ahleyani, M. Ahleyani (Journal of Language, Literature and Teaching, 2025)
The integration of STEM (Science, Technology, Engineering, and Mathematics) vocabulary into English Language Teaching (ELT) is becoming increasingly crucial in higher education, particularly for engineering students who must engage with global technical literature and communication. This study explores the challenges and opportunities in incorporating renewable energy-related vocabulary into the English curriculum of the Department of Electrical Engineering at the University of Mataram. Through a mixed-methods approach involving a needs analysis, classroom observations, and interviews with students and instructors, the research identifies key linguistic gaps, pedagogical constraints, and resource limitations. Simultaneously, the study highlights the potential of local renewable energy contexts such as solar, wind, and micro-hydro systems in West Nusa Tenggara as culturally relevant entry points for vocabulary acquisition. The findings suggest that embedding STEM vocabulary within project-based and content-based instruction not only enhances technical language proficiency but also fosters students' critical awareness of sustainable energy development in their region. This paper concludes with pedagogical recommendations for curriculum designers and English instructors aiming to align ELT more closely with the needs of engineering disciplines.